Cytotoxicity and genotoxicity of 1,4-bisdesoxyquinocetone, 3-methylquinoxaline-2-carboxylic acid (MQCA) in human hepatocytes - Zhang, Keyu; Ban, Manman; Zhao, Zhanzhong; Zheng, Haihong; Wang, Xiaoyang; Wang, Mi; Fei, Chenzhong; Xue, Feiqun (Research in veterinary science, 2012)
Quinoxaline-1,4-dioxides, widely used as medicinal feed additives as antibacterial growth promoters, have been shown to exert diverse toxicities. Their toxicities are hypothesized to be closely related to the formation of N-oxide reductive metabolites. 1,4-Bisdesoxyquinocetone and MQCA are important N-oxide reductive metabolites of quinocetone or olaquindox. In this study, we evaluated the cytotoxicity and genotoxicity of the metabolites, 1,4-bisdesoxyquinocetone and MQCA, as well as their parental drugs (quinocetone and olaquindox) in two human hepatocyte cell lines, L-02 and Chang liver cells. All these compounds inhibited the growth of cells in a dose-dependent and time-dependent manner by the MTT assay. Hormesis effects were found in L-02 cells treated with quinocetone at low doses. In the comet assay, although the two metabolites induced dose-related DNA damage in both cell lines, the levels of damage were less than that demonstrated for the parent drugs. The flow cytometric analysis showed that only the two metabolites induced cell cycle arrest at the S phase, and a decrease in the G0/G1, G2/M phase of Chang liver cells, which was not found for the L-02 cells treated with any compounds. The results indicate that 1,4-bisdesoxyquinocetone and MQCA are toxic to L-02 and Chang liver cells, and provide important new information towards understanding the olaquindox and quinocetone toxic mechanisms.